DNA repair-related genes in sugarcane expressed sequence tags (ESTs) - R.M.A. Costa; W.C. Lima; C.I.G. Vogel; C.M. Berra; D.D. Luche; R. Medina-Silva; R.S. Galhardo; C.F.M. Menck; V.R. Oliveira (Genetics and Molecular Biology, 2001)
There is much interest in the identification and characterization of genes involved in DNA repair because of their importance in the maintenance of the genome integrity. The high level of conservation of DNA repair genes means that these genetic elements may be used in phylogenetic studies as a source of information on the genetic origin and evolution of species. The mechanisms by which damaged DNA is repaired are well understood in bacteria, yeast and mammals, but much remains to be learned as regards plants. We identified genes involved in DNA repair mechanisms in sugarcane using a similarity search of the Brazilian Sugarcane Expressed Sequence Tag (SUCEST) database against known sequences deposited in other public databases (National Center of Biotechnology Information (NCBI) database and the Munich Information Center for Protein Sequences (MIPS) Arabidopsis thaliana database). This search revealed that most of the various proteins involved in DNA repair in sugarcane are similar to those found in other eukaryotes. However, we also identified certain intriguing features found only in plants, probably due to the independent evolution of this kingdom. The DNA repair mechanisms investigated include photoreactivation, base excision repair, nucleotide excision repair, mismatch repair, non-homologous end joining, homologous recombination repair and DNA lesion tolerance. We report the main differences found in the DNA repair machinery in plant cells as compared to other organisms. These differences point to potentially different strategies plants employ to deal with DNA damage, that deserve further investigation. A identificação e caracterização de genes envolvidos com reparo de DNA são de grande interesse, dada a sua importância na manutenção da integridade genômica. Além disso, a alta conservação dos genes de reparo de DNA faz com que possam ser utilizados como fonte de informação no que diz respeito à origem e evolução das espécies. Os mecanismos relacionados à remoção de danos pelo reparo de DNA, bem como suas conseqüências biológicas, já são bem conhecidas em bactérias, leveduras e animais. Entretanto, no que diz respeito a organismos vegetais, ainda há muito a ser investigado. No presente trabalho, apresentamos a identificação dos genes envolvidos nas principais vias de reparo de DNA em cana-de-açúcar, através de uma análise de similaridade do banco de dados do projeto brasileiro Sugarcane Expressed Sequence Tag (SUCEST) com seqüências protéicas conhecidas disponíveis em outros bancos de dados públicos (National Center of Biotechnology Information (NCBI) e Munich Information Center for Protein Sequences (MIPS) Arabidopsis thaliana). Esta busca revelou que a gama de proteínas envolvidas no reparo de DNA em cana-de-açúcar é similar a de outros eucariotos. Mesmo assim, foi possível identificar algumas características interessantes encontradas apenas em vegetais, provavelmente em função do seu processo evolutivo independente. As vias de reparo de DNA aqui representadas incluem fotorreativação, reparo excisão de bases, reparo excisão de nucleotídeos, reparo mismatch, end-joinning não homólogo, reparo por recombinação homóloga e tolerância a lesões. Este trabalho descreve as principais diferenças encontradas na maquinaria de reparo de DNA de células vegetais em relação àquela de organismos nos quais encontra-se bem descrita. Tais diferenças chamam a atenção para um potencial de mecanismos distintos em vegetais, que merecem futuras investigações.